Comparison of mid-term clinical outcome in heart transplantation patients using mycophenolate mofetil vs. enteric-coated mycophenolate sodium - Jeon, Kina; Kim, Darae; Choi, Jin-Oh; Cho, Yang Hyun; Sung, Kiick; Oh, Jaewon; Cho, Hyun Jai; Jung, Sung-Ho; Lee, Hae-Young; Park, Jin Joo; Choi, Dong-Ju; Kang, Seok-Min; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Mycophenolate mofetil (MMF) is a prodrug of mycophenolic acid (MPA) and a key immunosuppressant for improving graft survival in patients with heart transplantation (HTx). However, dose reduction or interruption is occasionally needed due to gastrointestinal (GI) side effects. Enteric-coated mycophenolate sodium (EC-MPS) is an alternative form of MPA delivery to improve GI tolerability. In the present study, the efficacy of EC-MPS compared with MMF in HTx patients was investigated. Methods In this retrospective study, the Korean Organ Transplant Registry (KOTRY) data were used to analyze the efficacy and rejection rate of MMF and EC-MPS. A total of 611 patients was enrolled from 2014 to February of 2021. Patients were divided based on the use of MMF or EC-MPS at 6 months post-HTx. Patients who were not prescribed MMF or EC-MPS were excluded. Graft survival, all-cause mortality, and treated rejection were compared between the two groups. All statistical analyses were performed using SPSS; characteristics were compared using Pearson chi-square test and survival rate with Kaplan-Meier plot and log-rank test. Results A total of 510 HTx patients was analyzed (mean age: 51.74 ± 13.16 years, males: 68.2%). At 6 months after HTx, 78 patients were taking EC-MPA (12.8%) and 432 patients were taking MMF (70.7%). The median follow-up was 42.0 months (IQR: 21.7–61.0 months). Post-HTx outcomes including overall survival, all cause mortality, acute cell mediated rejection (ACR), acute antibody mediated rejection (AMR), treated rejection, and cardiac allograft vasculopathy (CAV) were comparable between the two groups during follow-up. Conclusion Notable differences were not observed in overall survival, all cause mortality, ACR, AMR, treated rejection, and CAV between MMF and EC-MPS groups. Efficacy of EC-MPS was similar to that of MMF in HTx patients during mid-term follow up after HTx.